Engineering and Technology Based on Rapid Prototyping; Applied Mechanics and Materials; Vol. 770 : Urgent Problems of Up-to-Date Mechanical Engineering - Saprykin A. A. Aleksandr Aleksandrovich (Mechatronics, Automation and Control, 2015)
Title screen